Dielectric properties assessment of honey by using non-destructive dielectric spectroscopy - Aslina Abu Bakar; Muhammad Aiman Najmi bin Rodzali; Rosfariza Radzali; Azlina Idris; Ahmad Rashidy Razali (Institute of Advanced Engineering and Science, 2022)
In this research the dielectric constant of three types of Malaysian honey has been investigated using a non-destructive measurement technique. The objective of this research is to assess the dielectric constant of the three types of honey in Malaysia using a non-destructive measurement technique known as an open-ended coaxial probe in the frequency range from 100 MHz to 10 GHz frequency. Analysis on the effect water concentration in honey on the dielectric constant and the effect of temperature on dielectric constant of honey has been conducted. The three types of honey that have been chosen to be investigated in this project are stingless bee honey, wild honey and commercial (organic) honey and together their water adulterated samples. For this research, the probe had been set up by setting a range of frequency from 100 MHz to 10 GHz and needs to be calibrated with three calibration methods namely open, short and reference water. From the result it was found that the higher the temperature of the honey and the higher percentage of water content in the honey, the dielectric constant is increased. The dielectric constants of all honeys decreased with increasing frequency in the measured frequency range and increased with increase percentage of water content and temperature.